Screening of Potential Bacterial Isolates as Specific Biofertilizer Agent for Mungbean Plants (Research in Agriculture Livestock and Fisheries, 2020)
The Experiment was performed under glass house condition (24°8´ N 90°0´ E) with eight rhizobial strains namely MBR-3, MBI-5, MBI-19, MBM-4, MBM-8, MBP-10, MBB-3 and MBJ-7 obtained from mungbean rhizosphere of different locations in Bangladesh and BINA MB-1 (a registered biofertilzer for mungbean) was used as standard check along with un-inoculated control to test their potentiality under glass house condition for mungbean. Result revealed that the higher plant growth, biochemical parameters, seed yield attributes and seed yield were recorded in three bacterial isolates viz., MBI-5, MBB-3 and biofertilizer, BINA MB-1 with being the highest in MBI-5. Therefore, the isolate MBI-5 may be used as commercial biofertilizer after few more trials in the different mungbean growing areas of BangladeshRes. Agric., Livest. Fish.7(2): 191-197,  August 2020